PEMETAAN PRESTASI SEKOLAH MENENGAH ATAS/KEJURUAN DIKOTA BANDAR LAMPUNG BERBASIS ANDROID - Fajri Reskanida; Kurnia Muludi (Jurnal Komputasi, 2016)
School is an institution that was specifically designed for teaching students under the supervision of teachers. School that basically as a tool to implement education is expected to make more advanced society. This system is aimed as an alternative media to facilitate students and people who want to get information about senior and vocational high schools located in Bandar Lampung. In this study, mapping the achievement of senior/vocational high school in Bandar Lampung was built based on android and by using Java programming language. Method used in this application is Waterfall, and designed by using Unified Modeling Language (UML). This application includes 127 schools in Bandar Lampung consisting of 64 senior high schools (SMA) and 63 vocational high schools (SMK). This application has a variety of data such as school achievements, the value of National Examination, school address, school pictures, coordinates point of school and telephone number that can assist users to find information and location of High School and Vocational School in Bandar Lampung. Result of the test that performed by using Equivalence Partitioning method indicates that management rules of system can run properly as its function and this system can provide information properly. Additionally, based on testing data, this application is included into the category of user friendly application with the average value of percentage of 84.11% (Very Good).Keywords: Geographic Information System, Mapping, Senior High School, VocationalHigh School, Android